Is there any benefit from surgery for giant-dumbbell spinal tumors with prolonged paraplegia and joints contractures? a rare case report - Mohamad Saekhu; Eka Susanto; Samsul Ashari; Setyowidi Nugroho (Neurologico Spinale Medico Chirurgico, 2022)
The lack of clarity about the opportunities for significant neurologic improvement, coupled with the risk of severe postoperative complications, decompression surgery for patients with giant tumors in the cervical spine accompanied by long-lasting advanced neurological deficits places a heavy moral burden on surgeons. Here we report a three-year follow-up after surgery for an immense spinal neurofibroma in which the patient was bedridden for the past fifteen years. Our findings suggest surgery remains beneficial for patients without major postoperative complications.